Unsuccessful support of holism - Guberman, Shelia (Advances in Social Sciences Research Journal, 2018)
D. Navon’s article “Forest before the trees” (1977) presented the theory of global precedence in support of philosophy of holism, the “primacy of the whole” principle. In this paper it will be shown that 1) the global precedence theory is built up from undefined notions (globality, locality, feature, element, and global structure), 2) each notions is assigned to many meanings, 3) the mathematical expressions are wrong, 4) the transformations of the mathematical formulas are illegal, 5) the logic of argumentation is broken. Despite all this Narvon’s article recruited dozens of followers, inspired hundred publications in top psychological journals, and is included in many textbooks and reviews. It is mentioned at 42,000 web sites. This paper also shows why Narvon’s article was widely accepted as proof of the wrong principle “The whole before the parts”. This phenomenon indicates that “something is rotten in the state of Denmark”.